Valuation Effects with Transitory and Trend Productivity Shocks - Nguyen, Ha (World Bank, Washington, DC, 2014)
In the past two decades, cross-border portfolio holdings of a large variety of assets have risen sharply. This has created an important role for changes in asset prices of a country's external assets and liabilities (i.e. "valuation effects") in affecting the country's net foreign asset position. Valuation effects are commonly thought as stabilizing: they counteract current account movements and mitigate the impact of the current account on the country's net foreign asset position. This paper shows that whether valuation effects are stabilizing or not depends critically on the nature of underlying productivity shocks. In response to transitory shocks, valuation effects are stabilizing; but in response to trend shocks, such effects amplify the impact of the current account on the net foreign asset position. These contrasting results arise because optimally smoothing consumers respond differently to a transitory shock than to a trend shock to income. The results are consistent with the pattern of external imbalances between the United States and other G.7 countries since the 1990s.